Properties of energy-effective lightweight concrete with shape-stable activated carbon/phase change material composites and scoria - Ustaoğlu, Abid; Bayram, Muhammed; Sari, Ahmet; Hekimogl, Gokhan; Erdoğmuş, Ertuğrul; Kizinievic, Olga; Gençel, Osman (Elsevier Sci Ltd, 2025)
As global energy demand continues to rise, improvement of energy-efficient composites in construction is becoming increasingly critical. This work investigates physico-mechanical, and thermal performances of lightweight cementitious composites enhanced with bio-activated wood based-activated carbon (WAC) and phase change materials (PCMs), specifically Lauric acid and Myristic acid. The PCM impregnated WAC was replaced with the scoria up to 30 %. This research evaluates the impact of combining WAC and PCM on cementitious composites' performance, focusing on critical parameters as compressive strength, thermal conductivity, porosity, and dry unit weight. Results show that unit weight and compressive strength gradually lessen as the proportion of WAC increases. Specifically, the LWC-WAC30 mixture demonstrates a 32.3 % lower dry unit weight and an 83.7 % lower compressive strength compared to the reference lightweight concrete (R-LWC). Although mechanical performance is reduced, the improved thermal behavior, including lower peak temperatures and minimized thermal fluctuations, shows that these composites remain well-suited for thermal energy storage (TES) and passive building applications. Thermoregulation experiments conducted in a controlled setting demonstrated the PCM's effectiveness in stabilizing internal temperatures, achieving decrement of peak room center temperatures of up to 4.58 degrees C for cycles of elevated ambient temperatures. Furthermore, study emphasizes the innovative application of WAC as a sustainable medium for PCM integration, presenting a novel strategy that utilizes natural materials to enhance thermal performance while preserving structural integrity. These results underscore the considerable potential for employing WAC-PCM composites within the construction sector, particularly in the creation of energy-efficient and resilient building materials.
Keywords: Lightweight concrete; Energy and energy efficiency; Renewable energy; Thermal regulation; Phase change material; Wood-based activated carbon